Amniotic membrane attenuates heterotopic ossification following high‐dose bone morphogenetic protein‐2 treatment of segmental bone defects. Issue 1 (27th March 2022) - Priddy, Lauren B.; Krishnan, Laxminarayanan; Hettiaratchi, Marian H.; Karthikeyakannan, Sukhita; Gupte, Nikhil; Guldberg, Robert E.
Abstract: Treatment of large bone defects with supraphysiological doses of bone morphogenetic protein‐2 (BMP‐2) has been associated with complications including heterotopic ossification (HO), inflammation, and pain, presumably due to poor spatiotemporal control of BMP‐2. We have previously recapitulated extensive HO in our rat femoral segmental defect model by treatment with high‐dose BMP‐2 (30 μg). Using this model and BMP‐2 dose, our objective was to evaluate the utility of a clinically available human amniotic membrane (AM) around the defect space for guided bone regeneration and reduction of HO. We hypothesized that AM surrounding collagen sponge would attenuate heterotopic ossification compared with collagen sponge alone. In vitro, AM retained more BMP‐2 than a synthetic poly(ε‐caprolactone) membrane through 21 days. In vivo, as hypothesized, the collagen + AM resulted in significantly less heterotopic ossification and correspondingly, lower total bone volume (BV), compared with collagen sponge alone. Although bone formation within the defect was delayed with AM around the defect, by 12 weeks, defect BVs were equivalent. Torsional stiffness was significantly reduced with AM but was equivalent to that of intact bone. Collagen + AM resulted in the formation of dense fibrous tissue and mineralized tissue, while the collagen group contained primarily mineralized tissue surrounded by marrow‐like structures. Especially in conjunction with high doses of growth factor delivered via collagen sponge, these findings suggest AM may be effective as an overlay adjacent to bone healing sites to spatially direct bone regeneration and minimize heterotopic ossification. Abstract : Use of bone morphogenetic proteins (BMPs) at supraphysiological concentrations can lead to complications including heterotopic ossification and inflammation. Therefore, investigation of biomaterials capable of localizing the growth factor to mitigate these adverse effects is crucial. The objective of this study was to evaluate the efficacy of amniotic membrane (AM) in attenuating heterotopic ossification with high‐dose BMP‐2 treatment of rat segmental bone defects. As hypothesized, heterotopic ossification surrounding bone defects was reduced with collagen sponge + AM compared with collagen sponge alone.